IMPLEMENTASI METODE BERCERITA DALAM PENDIDIKAN AGAMA ISLAM UNTUK MENINGKATKAN PUBLIK SPEAKING - Lestiani, Yunita; Arfa Ladamay, Ode Mohamad Man (Fakultas Agama Islam Universitas Muhammadiyah Luwuk, 2024)
Education is basically changing the attitudes and behavior of a person or group in an effort to mature humans through teaching or training. One of the educational methods in school teaching includes several methods, this method is the storytelling method. This research aims to determine the implementation of storytelling methods in Islamic religious education to improve the public speaking of grade 7 students at SMP Muhammadiyah 4 Giri. This research uses a qualitative method with a descriptive qualitative research type that uses data collection techniques through observation, interviews and documentation. This research discusses the application of storytelling methods in Islamic religious education learning which is motivated by the importance of using methods in learning to shape students' character in speaking in public. As a form of teaching that provides real examples through the characters in the stories that are created or told. This method of telling stories about Islam at SMP Muhammadiyah 4 Giri in cultivating the religious maturity of class 7b students has supporting factors including educators, the environment and learning resources.